The RSK Inhibitor BIX02565 Limits Cardiac Ischemia/Reperfusion Injury. (March 2016) - Shi, Xi; O'Neill, Margaret M.; MacDonnell, Scott; Brookes, Paul S.; Yan, Chen; Berk, Bradford C.
Aims: During ischemia/reperfusion (I/R), ribosomal S6 kinase (RSK) activates Na + /H + exchanger 1 (NHE1) by phosphorylating NHE1 at serine 703 (pS703-NHE1), which promotes cardiomyocyte death and injury. Pharmacologic inhibition of NHE1 effectively protects animal hearts from I/R. However, clinical trials using NHE1 inhibitors failed to show benefit in patients with acute myocardial infarction (MI). One possible explanation is those inhibitors block both agonist-stimulated activity (increasing I/R injury) and basal NHE1 activity (necessary for cell survival). We previously showed that dominant-negative RSK (DN-RSK) selectively blocked agonist-stimulated NHE1 activity. Therefore, we hypothesized that a novel RSK inhibitor (BIX02565) would blunt agonist-stimulated NHE1 and protect hearts from I/R. Methods and Results: Serum/angiotensin II-stimulated pS703-NHE1 was significantly decreased by BIX02565 in cultured cells. Intracellular pH recovery assay showed that BIX02565 selectively inhibited serum-stimulated NHE1 activity. Ischemia/reperfusion decreased left ventricular–developed pressure (LVDP; inhibited) to 8.7% of the basal level in non-transgenic littermate control (NLC) mouse hearts, which was significantly improved (44.6%) by BIX02565. Similar protection was observed in vehicle-treated, cardiac-specific DN-RSK-Tg mice (43%). No additional protective effect was seen in BIX02565-treated DN-RSK-Tg hearts. BIX02565 also improved LVDP in cardiac-specific wild-type (WT)-RSK-Tg mouse hearts (7.4%-40.9%, P < .01). Finally, Western Blotting results confirmed DN-RSK and BIX02565 significantly decreased I/R-induced pS703-NHE1. Conclusion: The RSK plays a crucial role in I/R-induced activation of NHE1 and cardiac injury. The RSK inhibition may provide an alternative target for patients with MI.